Lietuvių ir lenkų istoriografija apie lietuvių mitologiją XIX a. pirmoje pusėje - Beresnevičius, Gintaras (Literatūra, 2015)
The article discusses the short-term “project” – to write Lithuanian mythology of one of the most influential public organisations of the 19th century in Vilnius – shubravci, which was close to masons. The majority of shubravci were quite positive about the “project” – Poles, Vilnius University professors – and chose pseudonyms of Lithuanian mythology characters by making a promise to collect material about each character. This rather marginal project among such people – the writing of mythology – was discussed in the publication Street News, Wiadomości brukowe, the official approach of the union to this idea from very enthusiastic transformed into very unacceptable and even became the object of mockery. However, the impulse of shubravci was captured by a lot of Lithuanians of the first quarter of the 19th century; later this idea was developed from Simonas Daukantas to Kajetonas Neazabitauskis, from D. Poška, to whom the idea of Vilnius professors became a “lightning-conductor” to his previous works. This idea among shubravci was supported by two persons – K. Kontrimas ir J. Šimkevičius; reaction in the union itself was fast, the idea was abandoned and suppressed. We can also observe the moment when processes which led to T. Narbutas, J. I. Kraševskis, S. Daukantas till Jonas Basanavičius ideology; the processes which contributed to the birth of liberation ideology at the beginning of XX century and were reiterated in the 20th century in Romuva and Ethos ideology line, which is still alive.